The HPV-16 E5 protein Inhibits TRAIL- and FasL-Mediated apoptosis in human keratinocyte raft cultures - Kabsch, Kirsten; Mossadegh, Nina; Kohl, Annette; Komposch, Gerda; Schenkel, Johannes; Alonso, Angel; Tomakidi, Pascal (Intervirology, 2004)
By using raft cultures of the polyclonal HaCaT cell lines stably transfected either with E5 (HaCaT/E5) or the empty vector (HaCaT/pMSG) as reference, we investigated the effect of the human papillomavirus type 16 (HPV-16) E5 protein on apoptosis. In comparison to conventional monolayer cultures this model system allows analysis of apoptosis under more tissue-like conditions by mimicking the stratified organization of a normal surface epithelium. Apoptosis was triggered either by FasL or TRAIL. Execution of the death program was checked at early and late stages by monitoring procaspase-3 cleavage and DNA fragmentation, respectively. Rafts of E5-expressing keratinocytes were completely protected from apoptosis and showed a background of apoptotic cells as low as the untreated cultures. In contrast, the HaCaT/pMSG cultures revealed a dramatic increase in apoptotic cells upon ligand treatment throughout the epithelial compartment. We conclude that the presence of the HPV-16 E5 protein in our tissue-like model prevents FasL- or TRAIL-mediated apoptosis.